AUTHORIZATION FOR DOPING IN FACE OF COMPETITORS GENETIC INEQUALITIES (Fiep Bulletin - online, 2014)
We live a society in which overcoming our own limits is something so inherent to the human condition that frequently the line that separates the ethical and moral from the disturbing is tenuous. That said, it is no simple task to articulate the discomfort that attempts to improve the man bring us. There is a magical aura around the idea of a society free from the moral shackles that impede unlimited use of methods to "produce" the best specimens of ourselves. Whilst this paper does not intend to exhaust the matter, but perhaps open our mind to a different way of thinking, in which doping can compensate for the unequivocal genetic imbalance between competitors of the same modality.
Keywords: .